Fiqh Siyasa on War and Peace in Indonesia’s Post-Colonial Era: Analyzing Its Prospects and Challenges in the Sulawesi Region - Adnan, Adnan; Maula, Bani Syarif; Harahap, Najhan Parluhutan (Institut Agama Islam Negeri Curup, 2025)
This research explores the interpretation and application of Fiqh Siyasa principles on war and peace by Islamist movements in Sulawesi, focusing on post-colonial dynamics and modern Indonesian reform. Fiqh Siyasa regulates state-citizen relations and interactions with non-Muslims, though its provisions on war and peace have limited contemporary application due to European colonialism and Western constitutionalism. The study traces the evolution of Fiqh Siyasa in Sulawesi, examining how local movements interpret these principles amid historical influences like colonial legacies, local rebellions, and conservative Islamic ideologies. Groups such as MIT, Mujahedeen KOMPAK, KPPSI, FKAWJ, MMI, FPI, and HTI exhibit diverse interpretations: some advocate for an Islamic state through dār al-Islam, while others promote coexistence by reinterpreting dār al-harb. These varied perspectives create a fragmented and context-dependent application of Fiqh Siyasa. The research contributes to understanding how global Islamic jurisprudential concepts adapt to regional realities, enriching discourse on Islam and state relations in modern Indonesia